2013
DOI: 10.5301/jbm.2012.9582
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin S128R Gene Polymorphism in Gastric Cancer

Abstract: The E-selectin S128R C allele may confer an increased susceptibility to gastric cancer development and correlate with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…S128R E-selectin has been shown to bind nonfucosylated K562 cells and is able to bind neuraminidase treated HL-60 cells, both of which cannot bind to wild-type E-selectin, clearly demonstrating that this naturally occurring E-selectin mutant can bind ligands other than sLe x (Revelle et al 1996;Rao et al 2002). If selectin/sLe x were required for leukocyte trafficking, it would be expected that persons carrying this mutation would be protected from inflammation; in contrast however, the S128R mutation is associated with increased risk for coronary artery disease (Wenzel et al 1996;Ghilardi et al 2004), cancer (Nadi et al 2007;Khazen et al 2009;Liarmakopoulos et al 2012), and importantly with increases in leukocyte trafficking (Khazen et al 2009;Liarmakopoulos et al 2012). To date, several mouse models that have reduced ability to express sLe x structures or deletion of endothelial selectins have been produced.…”
Section: Dw Scott and Rp Patelmentioning
confidence: 99%
“…S128R E-selectin has been shown to bind nonfucosylated K562 cells and is able to bind neuraminidase treated HL-60 cells, both of which cannot bind to wild-type E-selectin, clearly demonstrating that this naturally occurring E-selectin mutant can bind ligands other than sLe x (Revelle et al 1996;Rao et al 2002). If selectin/sLe x were required for leukocyte trafficking, it would be expected that persons carrying this mutation would be protected from inflammation; in contrast however, the S128R mutation is associated with increased risk for coronary artery disease (Wenzel et al 1996;Ghilardi et al 2004), cancer (Nadi et al 2007;Khazen et al 2009;Liarmakopoulos et al 2012), and importantly with increases in leukocyte trafficking (Khazen et al 2009;Liarmakopoulos et al 2012). To date, several mouse models that have reduced ability to express sLe x structures or deletion of endothelial selectins have been produced.…”
Section: Dw Scott and Rp Patelmentioning
confidence: 99%
“…The S128R polymorphism (A>C variation), the most common SNP of the E-selectin gene, facilitates ligand binding, which in turn increases the adhesion of lymphoid and myeloid cells to the endothelium. The E-selectin S128R polymorphism is associated with an increased risk of several cancers including gastric [ 25 , 26 ], colorectal [ 27 ] and pancreatic [ 28 ] cancers. However, a very limited number of studies investigating the association of the E-selectin S128R polymorphism with breast cancer susceptibility have revealed contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…However, more experiments are required to verify the above. E-selectin, the protein encoded by the SELE gene, mediates the progression and invasion of GC through different mechanisms, including promoting angiogenesis by activating the Src-PI3K pathway [150,151]. A positive correlation has been observed in GC between the serum expression levels of circulating E-selectin and tumor progression and metastasis, leading to a poor prognosis [152][153][154][155].…”
Section: A a B Bmentioning
confidence: 99%
“…A positive correlation has been observed in GC between the serum expression levels of circulating E-selectin and tumor progression and metastasis, leading to a poor prognosis [152][153][154][155]. Liarmakopoulos et al [150] demonstrated that the E-selectin S128R C allele was related to dismal survival in GC patients.…”
Section: A a B Bmentioning
confidence: 99%